2017
DOI: 10.1038/s41598-017-00879-1
|View full text |Cite
|
Sign up to set email alerts
|

Male New Zealand robins (Petroica longipes) cater to their mate’s desire when sharing food in the wild

Abstract: In many species that have bi-parental care, food-sharing males provide vital nutritional resources to their mates during reproduction. However, it is currently unknown whether females can signal specific desires to their mates, or if males can cater to female desire in the wild. Here we investigate whether and how wild male North Island robins (Petroica longipes) respond to changes in their mates' desires and nutritional need when sharing food. We demonstrate that wild female robins' desire for particular food… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 25 publications
1
4
0
Order By: Relevance
“…These findings corroborate findings on another corvid, Eurasian jays 31 and yet another bird species, New Zealand robins 33 , and are at par with findings on chimpanzees 43 and capuchin monkeys 71 . The studies on the Eurasian jays, New Zealand Robins and chimpanzees, however, have also been shown to flexibly adjust their help/sharing based somehow on the current desire of their conspecific 31,33,43 . Whether azure-winged magpies can do so too requires further testing.…”
Section: Discussionsupporting
confidence: 88%
“…These findings corroborate findings on another corvid, Eurasian jays 31 and yet another bird species, New Zealand robins 33 , and are at par with findings on chimpanzees 43 and capuchin monkeys 71 . The studies on the Eurasian jays, New Zealand Robins and chimpanzees, however, have also been shown to flexibly adjust their help/sharing based somehow on the current desire of their conspecific 31,33,43 . Whether azure-winged magpies can do so too requires further testing.…”
Section: Discussionsupporting
confidence: 88%
“…Toutouwai regularly consume some of the largest invertebrates on earth [19] and will cache year round, with a peak in intensity in winter, particularly for males [20]. These bold and curious birds are highly territorial, traits that make wild, free-living individuals amenable to cognitive testing across a range of domains [21][22][23] as well as easily monitored during the breeding season [24]. During the austral winter (June 2016), we measured individuals' (N males = 36, N females = 27) performance in an associative-learning task in which a spatial cue signaled the presence of a reward [25].…”
Section: Resultsmentioning
confidence: 99%
“…GM-CSF/IL-6-based protocols induced much lower percentage CD209 + cells, and in the absence of PGE2, GM-CSF, and IL-6 induced a higher expression of CD206. Although more specific in mice, some studies suggested that CD206 is a marker of human M2 macrophages generated from monocytes in the presence of M-CSF, but not in the presence of GM-CSF knowing to induce M1 type macrophages ( 54 , 55 ). In contrast, other reports suggested that high expression of CD209 better correlates with the M2 phenotype of human macrophages ( 56 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, GM-CSF/IL-6 M-MDSC also produced increased levels of IL-10 and displayed suppressive capacity in the co-cultures with allogeneic PBMC and T cells, all of which mark M2 type macrophages ( 54 , 55 , 58 ). Unlike the standard protocols for macrophages differentiation ( 54 56 ), we used IL-6 and IL-6/PGE2 from the beginning of differentiation, and about 23% and 43% of these cells, respectively, lacked the expression of HLA-DR, which is the main reason for designating them as M-MDSC, rather than macrophages. It is not clear at the moment whether additional stages of myeloid cell differentiation are present in our M-MDSC population and to which extent.…”
Section: Discussionmentioning
confidence: 99%